If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -1(2c + 2) = 2c(c + 2) + 3c Reorder the terms: 13 + -1(2 + 2c) = 2c(c + 2) + 3c 13 + (2 * -1 + 2c * -1) = 2c(c + 2) + 3c 13 + (-2 + -2c) = 2c(c + 2) + 3c Combine like terms: 13 + -2 = 11 11 + -2c = 2c(c + 2) + 3c Reorder the terms: 11 + -2c = 2c(2 + c) + 3c 11 + -2c = (2 * 2c + c * 2c) + 3c 11 + -2c = (4c + 2c2) + 3c Reorder the terms: 11 + -2c = 4c + 3c + 2c2 Combine like terms: 4c + 3c = 7c 11 + -2c = 7c + 2c2 Solving 11 + -2c = 7c + 2c2 Solving for variable 'c'. Combine like terms: -2c + -7c = -9c 11 + -9c + -2c2 = 7c + 2c2 + -7c + -2c2 Reorder the terms: 11 + -9c + -2c2 = 7c + -7c + 2c2 + -2c2 Combine like terms: 7c + -7c = 0 11 + -9c + -2c2 = 0 + 2c2 + -2c2 11 + -9c + -2c2 = 2c2 + -2c2 Combine like terms: 2c2 + -2c2 = 0 11 + -9c + -2c2 = 0 Factor a trinomial. (1 + -1c)(11 + 2c) = 0Subproblem 1
Set the factor '(1 + -1c)' equal to zero and attempt to solve: Simplifying 1 + -1c = 0 Solving 1 + -1c = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1c = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1c = 0 + -1 -1c = 0 + -1 Combine like terms: 0 + -1 = -1 -1c = -1 Divide each side by '-1'. c = 1 Simplifying c = 1Subproblem 2
Set the factor '(11 + 2c)' equal to zero and attempt to solve: Simplifying 11 + 2c = 0 Solving 11 + 2c = 0 Move all terms containing c to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 2c = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 2c = 0 + -11 2c = 0 + -11 Combine like terms: 0 + -11 = -11 2c = -11 Divide each side by '2'. c = -5.5 Simplifying c = -5.5Solution
c = {1, -5.5}
| 216=8(5a+71) | | 9x-10y=-1 | | 5(x+2)=8x+1 | | 4x^4+10x^3y-6x^2y^2=0 | | log(2)(7x+6)=3 | | (2x-5y)-(x+y)= | | 6x+4=6x-3 | | 1.75x^3+2.5x^2=6.25x | | -17+x=63 | | (3x+5)-7=42 | | 4(1+4n)=-124 | | 3x+6=4x-17 | | 27x+9y=54 | | 4x-6-9x+1=0 | | 8(x-6)=-88 | | -3x+36=-18 | | 6b^2+13b-63= | | 3/4*2/7= | | 8*9n=96 | | 19-(2x+3)=2(x+3) | | 2(x+1)=3x-15 | | 10y-2=3y+33 | | 3(5+4b)-2=0 | | 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W |